Plasma cholinesterase and carboxylesterase activities and nuclear and mitochondrial lipid composition of human placenta associated with maternal exposure to pesticides - Vera, Berta (2012)
Blood cholinesterases and tissue carboxylesterases (CEs) are sensitive indicators of environmental organophosphate pesticides (OPs) exposure. The aim of this pilot study was to assess the impact of OP exposure on placental CE activity and lipid composition. We performed a study of 40 healthy women who live in agricultural farms. Samples were collected during the pulverization period (PP) and recess period (RP). The plasma cholinesterase and placental CE activity decreased in PP, suggesting that women were exposed to OPs and that these pesticides reached the placenta. The cardiolipin content increased and the phosphatidylethanolamine content decreased in the light mitochondrial fraction while total cholesterol and sphingomyelin increased in the nuclear fraction. These changes in lipid profiles suggest repair by hyperplasia of the cytotrophoblast. Decreased CE activity may have clinical and toxicological implications and thus entail potential risks to damage fetal growth and development.